Alternative Formula for the Series of Consecutive m-Squares under Alternating Signs - Leomarich F Casinillo; Leo A Mamolo (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2020)
AbstractThis paper developed a simple but elegant formula for the series of consecutive square of natural numbers under alternating signs. Furthermore, this study investigated the said formula under odd and even number of terms and discuss some important results.Keywords: consecutive -squares; alternating signs; odd and even terms. AbstrakDalam paper ini kita membangun formula yang sederhana namun elegan untuk menghitung jumlah deret berganti-tanda dari kuadrat bilangan-bilangan asli berurutan.  Kita akan menyelidiki formula untuk kasus banyaknya suku ganjil maupun genap dan mendiskusikan beberapa hasil yang penting.Kata kunci: -kuadrat berurutan; berganti-tanda; bersuku ganjil dan bersuku genap.